The effect of the application of the contextual learning model on the ability of short story writing for class VII SMP - Bakri, Muhammad (International research journal of management, IT and social sciences, 2021)
This study aimed to determine the effect of applying a contextual learning model on short story writing skills for seventh-grade students of SMP Negeri 35 Makassar. This type of this study was experimental research with quantitative analysis techniques that were numbered from the quick writing ability test results. The result of the data analysis showed that the average score of the control class was 51.34, and the experimental class was 79.24. T-test showed that the value of the t-count was more significant than the t-table. T-count was 2,790, and the t-table was 2,021. It can be concluded that H1 is accepted. So, applying the contextual learning model can significantly affect students' abilities in writing a short story.